EDUCATION OF TECHNICAL SUBJECTS SUPPORTED BY CAX APPLICATIONS - DVOŘÁK, Karel (Journal of Technology and Information Education, 2011)
CAx (CAD, CAE, CAM) technologies represent progressive tools for technical production planning. Didactic potential of these applications for teaching of professional technical engineering oriented subjects can be utilized in education. Teaching supported by the use of this category of information technologies is the way how to improve knowledge and skills of students of technical specializations.
Keywords: design; engineering; manufacturing; virtual prototype; 3D data model; assembly